School Productivity in Increasing the Profitability of the Integrated Islamic Junior High School Foundation in the Riau Islands Province - Yudiarta Rustam; Mukhtar Latif; Ahmad Ridwan (Maneggio, 2026)
School productivity serves as a primary determinant of operational sustainability for Islamic educational foundations in the modern era. In Riau Islands Province, Islamic educational institutions face distinctive challenges related to the archipelagic geographical conditions that affect accessibility and distribution of educational resources. This study aims to explore school productivity in enhancing foundation profitability at Integrated Islamic Junior High Schools, identify factors influencing their relationships, and develop effective and sustainable management models. The research employs a qualitative approach with a descriptive-evaluative case study design at three Integrated Islamic Junior High Schools: SMP IT Ulil Albab Batam, SMP IT As Sakinah Tanjungpinang, and SMP IT Bahtera Insani Bintan. Data were collected through in-depth interviews, non-participant observation, and documentation over six months, then analyzed using the interactive model of Miles et al. (2020). Research findings identify six indicators of school productivity: resource optimization, academic achievement, Islamic character formation, global competitiveness, financial sustainability, and management system integration. Findings indicate that educational success is not solely determined by the availability of modern facilities, but rather depends on principals' managerial capacity and work culture grounded in Islamic principles such as al-ihsan, amanah, shura, and tawazun. The three schools demonstrate different yet equally effective productivity models: digital-professional, collaborative-character, and creative-adaptive. The research confirms that Islamic education can adapt to globalization demands without abandoning spiritual identity, through integrating 21st-century skills with Islamic values ​​to achieve academic excellence while contributing positively to society.